2016
DOI: 10.1002/ajpa.22982
|View full text |Cite
|
Sign up to set email alerts
|

Conarticular congruence of the hominoid subtalar joint complex with implications for joint function in Plio‐Pleistocene hominins

Abstract: Joint curvature indices are better discriminators than joint surface area indices, which may reflect a greater contribution of rotation, rather than translation, to joint movement in plantigrade taxa due to discrepancies in conarticular congruence and the "convex-concave" rule. The pattern of joint congruence in Au. sediba contributes to other data on the foot and ankle suggesting that the lateral side of the foot was more mobile than the medial side, which is consistent with suggestions of increased medial we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 89 publications
(195 reference statements)
3
31
0
Order By: Relevance
“…To interpret fossil specimens, it is essential to have a thorough understanding of the morphological correlates of known locomotor behaviors in extant species (e.g., Stern & Susman, Stern Jr. & Susman, 1983; DeSilva et al, 2013; Ruff, Burgess, Ketcham, & Kappelman, 2016; Marchi, Harper, Chirchir, & Ruff, 2019). Deciphering these relationships in the foot and ankle is vital because of their role in weight‐bearing and direct contact with the substrate during locomotion (e.g., DeSilva & Throckmorton, 2010; Prang, 2016a, 2016b; Zeininger, Patel, Zipfel, & Carlson, 2016). This is especially important in relation to hominin evolution because of the specialized nature of the human foot (e.g., Morton, 1922).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To interpret fossil specimens, it is essential to have a thorough understanding of the morphological correlates of known locomotor behaviors in extant species (e.g., Stern & Susman, Stern Jr. & Susman, 1983; DeSilva et al, 2013; Ruff, Burgess, Ketcham, & Kappelman, 2016; Marchi, Harper, Chirchir, & Ruff, 2019). Deciphering these relationships in the foot and ankle is vital because of their role in weight‐bearing and direct contact with the substrate during locomotion (e.g., DeSilva & Throckmorton, 2010; Prang, 2016a, 2016b; Zeininger, Patel, Zipfel, & Carlson, 2016). This is especially important in relation to hominin evolution because of the specialized nature of the human foot (e.g., Morton, 1922).…”
Section: Introductionmentioning
confidence: 99%
“…Other work has shown that subtalar joint conarticular curvature is higher in more arboreal species, allowing for greater joint mobility (Prang, 2016b). This is supported by the finding that the posterior talar facet is more curved in orangutans than the other great apes (Prang, 2016a). Little work, however, has been done to explore great ape calcaneal variation without including modern humans in the sample, and never within a single genus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in both anthropoids and primates more broadly, cuboid facet surface area is significantly correlated with body mass; however, we do not know if this is an isometric or allometric relationship (Yapunich, Gladman, & Boyer, 2015). Human and nonhuman primate anterior/ middle talar facet and posterior talar facet curvatures, however, do not exhibit significant relationships with species average body masses (Prang, 2016b). Among modern humans, lateral plantar process width is positively correlated with body mass, but the exact nature of the scaling relationship is unclear (Gill, Taneja, Bredella, Torriani, & DeSilva, 2014).…”
Section: Calcaneal Morphology and Body Sizementioning
confidence: 81%
“…Morton's early 1920s publications in the AJPA on comparative foot anatomy and function (Morton, ) are classics in the field and have stimulated much further research (Gebo, ) (also see Larson, this volume). These papers also began a string of early publications in the journal on the evolution, growth and development, functional morphology, and kinematics of the foot (Dougan, ; McMurrich, ; Patek, ; Straus, ; Weidenreich, ), a focus that obviously extends to the present day (Holowka, O'Neill, Thompson, & Demes, ; Prang, ; Young & Heard‐Booth, ). As pointed out by Morton (), this continuing interest stems in part from the fact that the foot represents the point of contact of the body with the substrate (in bipeds), and thus should reflect, as much or more than any other structure, functional adaptations to changes in locomotion.…”
Section: Early Years (1918–1939)mentioning
confidence: 99%